2008
DOI: 10.1007/s10695-008-9220-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in some components of the muscle lipids of three freshwater fish species under natural extreme cold and temperate conditions

Abstract: Fatty acid composition, conjugated linoleic acid and cholesterol contents in the muscles of three freshwater fish species (Barbus plebejus escherichi, Capoeta capoeta capoeta and Rutilus rutilus) were determined under natural extreme temperate (July) and cold (January) conditions. The aim of the study was to determine whether there were differences in these components of the muscle lipids among these three fish species under extreme natural conditions. Samples were analyzed using gas chromatography. Palmitic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 48 publications
5
10
1
Order By: Relevance
“…The highest and lowest levels of this acid in the NL fractions were determined in the livers of C. sieboldii (3.18%) and C. baliki (0.98%), respectively. This result seems compatible with the data that phospholipids are depots of C20:4 n-6 in the biological membranes (TOCHER et al, 2008) and the metabolism of this acid, participating in cell signalling events, results in the production of pharmacologically active eicosanoids (UYSAL et al, 2008;LE et al, 2009). However, C18:2 n-6 was other notable fatty acid exceeding 1% in the NL fractions of all groups.…”
Section: Fatty Acid Compositions Of Neutral Lipids (Nl) and Polar Lipsupporting
confidence: 91%
“…The highest and lowest levels of this acid in the NL fractions were determined in the livers of C. sieboldii (3.18%) and C. baliki (0.98%), respectively. This result seems compatible with the data that phospholipids are depots of C20:4 n-6 in the biological membranes (TOCHER et al, 2008) and the metabolism of this acid, participating in cell signalling events, results in the production of pharmacologically active eicosanoids (UYSAL et al, 2008;LE et al, 2009). However, C18:2 n-6 was other notable fatty acid exceeding 1% in the NL fractions of all groups.…”
Section: Fatty Acid Compositions Of Neutral Lipids (Nl) and Polar Lipsupporting
confidence: 91%
“…C18:1 n-7 levels varied between 4.73% (liver) and 5.98% (intestine). Rahnan et al (1995) and Uysal et al (2008) revealed that MUFA concentrations in freshwater fish were higher than the proportions of PUFAs and SFAs and that C18:1 n-9 was the major component of the MUFA fraction. Kalyoncu et al (2009) reported similar results in the muscle of V. vimba, in which MUFA levels were found to be higher than PUFAs and SFAs in all seasons investigated.…”
Section: Fatty Acid Composition Of Total Lipidmentioning
confidence: 99%
“…However, higher levels of DHA were determined in the PLs of the liver (5.67%), muscle (17.37%), and intestine (4.35%). High levels of DHA in the PLs can be explained by considering that PLs are the main resources used by fish to adapt to environmental changes by ensuring constant fluidity of the biological membranes, and one of the strongest candidates for this purpose is specifically DHA (Uysal et al, 2008). The n-3/n-6 ratios in the NLs were determined to be 1.33 in the liver, 1.56 in the muscle, and 1.25 in the intestine.…”
Section: Fatty Acid Composition Of Neutral and Polar Lipid Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, average n-6/n-3 was found as 0.27. Comparing to some marine fish species studied by Özoğul and Özoğul (2007a) bogue (boops boops) (0.05), mullet (mugil cephalus) (0.12), sardine (sardinella aurita) (0.11) and scad (trachurus mediterraneous) (0.04) and some fresh water species studied by Uysal et al, (2008) Barbus plebejus escherichi (0.37) Capoeta capoeta capoeta (0.37) and Rutilus rutilus (0.56) n-6/n-3 ratio of our study was higher than marine species, lower than freshwater species, as a result, being under the maximum recommended value, consumption of pearl mullet has an advantageous impact on maintaining the necessary dietary n-6/n-3 ratio at the recommended level. Revealing the nutritional value of fish, n-3/n-6 is recommended as a good index (Pigott and Tucker, 1990).…”
Section: Resultsmentioning
confidence: 86%